Les régulations interactives et l’engagement des élèves : des soutiens à l’apprentissage - Catherine Tobola Couchepin (Éducation et Socialisation)
This communication focuses on teacher’s assessment and regulation to support the learning of students in the context of a written production of an argumentative text. The methodology relies on student results to identify the underdlying professional practices. The multifocal analysis shows significant progress for all students. It highlights the language and the meanings shared in the teacher-student relationship.